Is the participation in the non-farm income generating activities help smooth food consumption? Evidence from rural Nigeria - Jabo, Mohammad Sani Muhammad; Ismail, Mohd Mansor; Abdullah, Amin Mahir; Shamsudin, Mad Nasir (Australian Academy of Business and Social Sciences, 2014)
More than 40 percent of the total income of households in rural Nigeria is from non-farm activities. However, there has been no much empirical work to analyse whether the participation in these activities reduces food insecurity and smooth food consumption or not. This paper examines the impact of non-farm diversification on food consumption expenditure using a national representative sample of 3624 rural households from the General Household-panel Survey data. The propensity score matching technique was employed in the analysis to take care of selection bias. We find that the on the average food consumption expenditure of the non-participating households in NFIGA is less than participating households. Overall, the average increase in food expenditure due to diversification into non-farm income generating activities range between ₦1571.52 to ₦11654.07.